CONTENT SYSTEM OF LINGUISTIC CODES (Scientific journal of the Fergana State University, 2024)
This article covers the importance of cultural codes in the study of linguoculturalogy, as well as the content system of linguocultural codes and the classifications of scientists based on different approaches to the nature of the codes by meaning. Today, linguoculturalogy has found that there are a huge number of types of codes, and their specific linguistic features are analyzed on the basis of examples.